Exploring the Critical Thinking Structures of Low-Achieving Students in Solving Algebra HOTS Tasks - Hendra Kartika; Daiki Urayama; Siti Mutmainah; Hodiyanto Hodiyanto (EDUPEDIA PUBLISHER, 2026)
Purpose: Low achievement in mathematics remains a critical concern in supporting students’ meaningful learning and cognitive development. This study explored the critical thinking skills of junior high school students with low mathematics achievement. Specifically, the study aimed to identify the structures of students’ critical thinking based on the FRISCO framework, encompassing Focus, Reasons, Inference, Situation, Clarity, and Overview. Methodology: This study adopted a qualitative case study design to provide an in-depth understanding of students’ critical thinking structures. Ten seventh-grade students with low mathematics achievement were purposively selected as participants. Data were collected through open-ended algebraic Higher-Order Thinking Skills (HOTS) tasks and semi-structured follow-up interviews. The collected data were subsequently analyzed using content analysis to identify patterns and characteristics of students’ critical thinking processes. Findings: The findings indicate that most participants encountered substantial difficulties in identifying core problems, recognizing procedural errors, providing justification, and formulating valid conclusions. Two dominant patterns emerged: (1) absence of focus accompanied by invalid reasoning and false inference; and (2) presence of focus without adequate reasoning, with limited inferential coherence. Significance: These findings indicate that students’ critical thinking remains insufficiently developed and point to the need for more systematic and structured pedagogical support in algebraic HOTS contexts.